Pro Tools 9 : the mixer's toolkit - Adam, Nathan (Focal Press, 2011)
In this exciting new book learn the secret toolkits used to to develop a professional, radio-ready rock mix out of tracks recorded in a garage. In Pro Tools 9: The Mixers Toolkit you will get hands-on with a real Pro Tools session as you start arranging, EQing, compressing, bussing, effecting and automating a modern demo into a hard hitting, radio ready production. See the in-depth use of micro-editing, Elastic Time, and Beat Detective across Drums, Bass, Guitars and Vocals, and learn how to use Multi-Compression, Reverbs and Delays to make your tracks really jump out of a mix. Finalize your production with pre-mastering tips to get a loud mix that will stand up to the competition. As you go through you'll discover dozens of Pro Tools 9 features and shortcuts, as well as tricks that can be applied to any workstation. With an interactive website including hi-definition video tutorials, you will also watch, listen, edit and mix alongside these award winning Pro Tools engineers. This is a fantastic text showing you two engineers personal workflow for making a killer rock music mix. Take your Pro Tools skills to the next level with Pro Tools 9: The Mixers Toolkit today. This book contains hundreds of pages and illustrations outlining every step of a modern mix including: Buss Mixing, Parallel Compression, and getting tight rhythm tracks Delay tricks and Vocal Automation for clarity and punch Techniques for Pre-Mastering the Final Mix.